2012
DOI: 10.2174/138920012803762783
|View full text |Cite
|
Sign up to set email alerts
|

Yeast as a Humanized Model Organism for Biotransformation-Related Toxicity

Abstract: High drug attrition rates due to toxicity, the controversy of experimental animal usage, and the EU REACH regulation demanding toxicity profiles of a high number of chemicals demonstrate the need for new, in vitro toxicity models with high predictivity and throughput. Metabolism by cytochrome P450s (P450s) is one of the main causes of drug toxicity. As some of these enzymes are highly polymorphic leading to large differences is metabolic capacity, isotype-specific test systems are needed. In this review, we wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 148 publications
(197 reference statements)
0
12
0
Order By: Relevance
“…The experimental model S. cerevisiae has been widely used in biomedical research studies, with very diverse objectives and applications, from cellular biology involved in genetic and neurological diseases [43] to toxicological surveys [44]. The broad applicability of this yeast species as a model organism is based on its easy cell cycle control, great facility of biochemical and genetic manipulation, short time, and inexpensive reproducible experiments [45] as well as biochemical and genetic similarity to animal cells [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…The experimental model S. cerevisiae has been widely used in biomedical research studies, with very diverse objectives and applications, from cellular biology involved in genetic and neurological diseases [43] to toxicological surveys [44]. The broad applicability of this yeast species as a model organism is based on its easy cell cycle control, great facility of biochemical and genetic manipulation, short time, and inexpensive reproducible experiments [45] as well as biochemical and genetic similarity to animal cells [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to S. cerevisiae and K. lactis, which are widely used for molecular biology and industrial applications (Mattiazzi et al, 2012;Schaffrath and Breunig, 2000;Schwimmer et al, 2006;Smith and Snyder, 2006;van Leeuwen et al, 2012), K. marxianus has received relatively little attention, although there are an increasing number of reports describing the potential application of K. marxianus for the production of ethanol, biomass, endogenous enzymes and aromatic compounds (Bansal et al, 2008;Fonseca et al, 2008;Gao and Daugulis, 2009;Limtong et al, 2007;Nonklang et al, 2008Nonklang et al, , 2009Rodrussamee et al, 2011;Wittmann et al, 2002) and for protein structural analysis (Watanabe et al, 2012;Yamaguchi et al, 2012aYamaguchi et al, , 2012b. Thus, in the present study, we generated and characterized 79 auxotrophic mutants and identified 35 complementing genes using a novel integrative transformation approach for the development of genetic tools in K. marxianus.…”
Section: Discussionmentioning
confidence: 99%
“…The budding yeast Saccharomyces cerevisiae is frequently used to study drug-induced toxicity [18,19]. Although it is a simple eukaryotic cell with approximately 6000 genes, many essential pathways are highly conserved between human and yeast.…”
Section: Introductionmentioning
confidence: 99%